Prevention of haemophilic arthropathy during childhood. May common orthopaedic management be extrapolated from patients without inhibitors to patients with inhibitors? - Rodriguez-Merchan, E; Hedner, U; Heijnen, L; Jimenez-Yuste, V; Lee, C; Morfini, M; Querol, F; Roosendaal, G; Santagostino, E; Solimeno, L (2008)
We recommend prophylaxis in haemophilic children with an inhibitor as a way of preventing the musculoskeletal impairment that is likely to affect them. This approach has been used for children without inhibitors with excellent results. If prophylaxis is not feasible, we suggest that intensive on-demand treatment should be given. Two agents, recombinant activated FVII (rFVIIa) and activated prothrombin complex concentrates (aPCC), are currently used to control haemostasis either for prophylaxis or intensive on-demand treatment. As it is recombinant, rFVIIa would seem more appropriate to be employed in children. aPCC could be used in adults, or in the event of an unsatisfactory response to rFVIIa. We recommend prophylaxis or, at least, intensive on-demand treatment in haemophilia children with inhibitors. Both rFVIIa and aPCC are being used for this purpose. It would seem that rFVIIa might be more appropriate for children as it is a recombinant product. Nevertheless, after skeletal maturity (in adults), both agents could be used indistinctively (taking into consideration that FEIBA is a plasma-derived product). We still need more well-designed comparative studies in order to be able to assert that our consensus-based conclusion is evidence based. In orthopaedic surgery, both aPCC and rFVIIa have been reported to be effective in controlling perioperative haemostasis, although in practice most centres have so far used rFVIIa for their orthopaedic procedures. We recommend rehabilitation programmes for all patients with inhibitors in order to mitigate the disabling and handicapping impact of their condition and thereby enable them to achieve social integration. Programmes for haemophilic children without inhibitors can be applied to children with inhibitors but should be individually tailored.